2023
DOI: 10.3390/su15118702
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities of IoT in Fog Computing for High Fault Tolerance and Sustainable Energy Optimization

A. Reyana,
Sandeep Kautish,
Khalid Abdulaziz Alnowibet
et al.

Abstract: Today, the importance of enhanced quality of service and energy optimization has promoted research into sensor applications such as pervasive health monitoring, distributed computing, etc. In general, the resulting sensor data are stored on the cloud server for future processing. For this purpose, recently, the use of fog computing from a real-world perspective has emerged, utilizing end-user nodes and neighboring edge devices to perform computation and communication. This paper aims to develop a quality-of-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…These terms are integrated because of the ongoing effort to reduce energy consumption in smart devices and sustainable spaces. However, due to the large amount of data exchanged and the potential distances and data sources involved, a data storage model outside the cloud and closer to the source may be beneficial for future network and wireless sensor architectures [1,13,73]. During the same time period, the terms 'smart farms', 'health care', and 'smart cities' emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These terms are integrated because of the ongoing effort to reduce energy consumption in smart devices and sustainable spaces. However, due to the large amount of data exchanged and the potential distances and data sources involved, a data storage model outside the cloud and closer to the source may be beneficial for future network and wireless sensor architectures [1,13,73]. During the same time period, the terms 'smart farms', 'health care', and 'smart cities' emerged.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Reyana et al [13] demonstrated the potential of fog computing to enhance fault tolerance and energy efficiency in IoT systems. Their study highlights the role of cloud computing in creating sustainable and efficient IoT environments.…”
Section: Introductionmentioning
confidence: 99%
“…Verification and validation (V&V) techniques are crucial for ensuring the quality, reliability, and security of software systems in the context of IoT and cloud computing [82,83]. These systems involve a complex network of devices, sensors, and services that must work together seamlessly and securely [84].…”
mentioning
confidence: 99%